Tuberculosis in kidney transplant recipients: A case series - Anand, Manish (World J Transplant, 2017)
Solid organ transplant recipients have an elevated risk of tuberculosis (TB) with high mortality. Data about TB in this population in the United States is sparse. We present four cases of active tuberculosis in kidney transplant recipients at our center. All patients had possible TB exposure prior to transplant and all were diagnosed with active TB within the first year of transplant. Disseminated TB was seen in half of the patients with extra-pulmonary TB being more common affecting lymph nodes, pericardium, and the kidney allograft. Delay in diagnosis from onset of symptoms ranged from fifteen days to two months. Two patients died from TB. TB is a largely preventable and curable disease. However, challenges remain in the diagnosis due to most recipients presenting with atypical symptoms. Physicians should maintain a high degree of suspicion for TB to promptly diagnose and treat post-transplant thereby minimizing complications. A review of the literature including the epidemiology, pathogenesis, clinical presentation, diagnosis and treatment options are discussed.